EFISIENSI PENGGUNAAN FAKTOR PRODUKSI PUPUK PADA TANAMAN CABAI DI DESA LINONGGASAI KECAMATAN WONGGEDUKU BARAT KABUPATEN KONAWE - Sarty Syarbiah (Jurnal Akrab Juara, 2019)
This research was carried out from March to May 2017. The research location was located in Linonggasai Village, Wonggeduku Barat District, Konawe District. The selection of research locations was done purposively, with the consideration that in Linonggasai Village, Wonggeduku Subdistrict, Konawe District was one of the regions that had very good potential in developing red chili farming. The factors that influence national chili production are infertile soil conditions due to continuous use. The right cultivation action is needed to get high crop production in such infertile soils. One of the actions that can be done is by fertilizing. The results of the analysis and discussion above can be drawn from the conclusion that the use of fertilizer production factors is not efficient on red chili farming in Linonggasai Village, Wonggeduku Barat District, Konawe District. This is indicated by an efficiency value that is not equal to one (NPMx â‰  1), namely; SP 36 efficiency value is 0.70, NPK Ponska efficiency value is 0.87, NPK Pearl efficiency value is 0.66 and efficiency value of liquid organic fertilizer is 2.07. This means that the use of fertilizer production factors on these farms is still very wasteful